Substitution of maize with rice bran and rice polish in the diet of Angora rabbits - BHATT, R S; SHARMA, S R; SINGH, UMESH; BHASIN, V (The Indian Journal of Animal Sciences, 2014)
An experiment was conducted on 30 adult German Angora rabbits, of either sex, divided in to 2 equal groups, to assess the effect of 2 experimental diets (T1 and T2 ), on the biological performance, wool yield, wool characteristics and mortality. Diet T1 consisted of maize - 30%, rice polish - 15%, rice bran - 15%, groundnut-cake - 20%, soyaflakes - 10%, molasses- 8 %, salt - 1 % and mineral mixture - 1 %, whereas in T2 diet, 15% of the maize (i.e.50% of the value in T1) was replaced with rice polish and rice bran (7.5% each). Both diets in mash form were fed, about 150g day-1 head-1 along with wilted grass mixture of rye grass (Lolium perenae), tall fescue (Festuca arundinacea) and white clover (Trifolium repens) ad lib, for a period of 225 days or 3 shearings. Body weights increased in both groups up to second shearing (150 days) and thereafter it decreased due to summer depression. However, final body weight in T1 and T2 were not significantly different from their respective initial body weights. Total dry matter intake (DMI) per animal was significantly (P <0.05) more in T2 as compared to T1. Wool yield in T1 and T2 groups during 1st, 2nd and 3rd shearing was nonsignificantly different from each other. Similarly, no significant difference in the wool characteristics - staple length, fibre diameter and guard hairs of both the groups could be observed. A mortality of 26.6% and 13.3% was recorded in T1 and T2 respectively. The differences for digestibilities of dry matter, crude protein, neutral detergent fibre and cellulose were nonsignificant whereas that of acid detergent fibre, hemicellulose were significant (P <0.05) in experimental groups. The difference for the balance of nitrogen in T1 and T21 was nonsignificant. From this experiment it can be concluded that substitution of maize (30% w/w in diet) in rabbit diet with low costing rice bran and rice polish (to the extent of its 50%), did not have any significant adverse effect on the body weight and wool production, till 3 shearings.